Protective Role of Sodium Chloride and Sodium Dithionite agains UV-B Induced Damage in Chlorella vulgaris - Prasad, Y.; Kumar, A.; Kumar, H.D D. (Ecoprint: An International Journal of Ecology, 2009)
Highly useful and economic algae especially protein-rich micro- algae are highly affected, and the protein, carbohydrate and pigments are highly damaged by increased UV-B exposure in a high protein-rich (45%),green,freshwater, unicellular,microalga Chlorella vulgaris. 1 mM sodium dithionite (SDT) partially protected survival and growth against UV-B induced damage but NaCI (0.5m) became lethal to C. vulgaris in supplemented condition. Key words: UV-B; Protection; Survival; Growth; Chlorella doi: 10.3126/eco.v13i0.1632 Ecoprint (An International Journal of Ecology) Vol. 13, 2006 Page:61-67